PENGARUH EFISIENSI MODAL KERJA DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Octavianty, Ellyn; Syahputra, Defi Jumadil (Universitas Pakuan, 2015)
Working capital and liquidity will affect the level of corporate profitability. If the working capital and liquidity levels increase the companys profitability will decline. This study aimed to determine the effect of working capital (working capital turnover, receivable turnover, inventory turnover,) and liquidity (current ratio). This research is about the effect of working capital and liquidity to profitability made on the Pharmaceutical Sector Sub listed on the Stock Exchange by using secondary data, purposive sampling method. The analytical method used inferential statistics, namely multiple linear regression analysis using SPSS version 20.Results of the study revealed the fact that 81.1% of profitability (return on assets) are influenced by working capital (working capital turnover, receivable turnover, inventory turnover) and liquidity (current ratio). While 18.9% is influenced by other variables not included in the regression model. Companys pharmaceutical sector has fluctuated development of working capital and the amount is not much, while the level of liquidity is quite good. This has resulted in a low level of profitability generated.Â Keywords: Efficiency Working Capital, Liquidity, Profitability